2018
DOI: 10.2478/hukin-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variations in Physical Performance: Are There Morning-to-Evening Differences in Elite Male Handball Players?

Abstract: The purposes of this study were to determine: 1) morning-to-evening differences in physical performance with and without a ball; and 2) associations between sleep outcomes (duration and quality) and physical performance in handball players. Sixteen elite, male handball players (25.4 ± 5.8 yr, 94.0 ± 7.4 kg, 193.5 ± 7.5 cm) completed physical performance tests without a ball (a zig-zag test assessing closed-skill agility, linear sprints, and countermovement (CMJ) and squat jumps) and with a ball (a zig-zag test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
4
11
0
1
Order By: Relevance
“…The participants reached higher jump heights in the evening than the morning. Pavlovic et al, (Pavlović et al, 2018) in support of our findings showed that jump heights followed by static stretching in warm-up were higher at the evening (18:00-19:30 h) compared to morning (08:00-09:30 h) in handball players. In another study used static stretching in warm-up showed that swimmers performed better in CMJ, 25m swimming time, maximal strength, and free weighted bench press in the evening (18:00 h) than morning (10:00 h) (Pallarés et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…The participants reached higher jump heights in the evening than the morning. Pavlovic et al, (Pavlović et al, 2018) in support of our findings showed that jump heights followed by static stretching in warm-up were higher at the evening (18:00-19:30 h) compared to morning (08:00-09:30 h) in handball players. In another study used static stretching in warm-up showed that swimmers performed better in CMJ, 25m swimming time, maximal strength, and free weighted bench press in the evening (18:00 h) than morning (10:00 h) (Pallarés et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Sessions were carried out at the same time of day (10:00–11:00 h) to avoid any effect of circadian rhythm on the measured variables. 18 All testing sessions were performed in similar environmental conditions (temperature: 15.3 ± 0.6 °C, humidity: 49.9 ± 6.8%) on the same indoor football court. The pitch size of all SSG was fixed at 40 × 20 m with consistent goal sizes (2 m high x 3 m wide).…”
Section: Methodsmentioning
confidence: 99%
“…In this Special Issue, one paper analyses the influence of fouls ( Fasol and Redlich, 2018 ), concluding that whether or not a game-stopping foul is committed has no influence on scoring a goal, and another looks at how home court advantage affects performance ( Pic, 2018 ), finding that the potential advantage of playing at home occurs mainly in situations in which the teams reach the end of the game tied. It has to be noted, however, that physical performance in handball is different in the morning from what it is in the evening ( Pavlović et al, 2018 ). Studies related to the national teams of two of the world’s major countries in this sport – Norway and Denmark – have confirmed that experience in the Norwegian national youth and junior teams is associated with the number of international matches played in the senior category ( Bjorndal et al, 2018 ), and that the relative age effect is apparent in Danish national men’s teams at these younger levels ( Wrang et al, 2018 ).…”
mentioning
confidence: 99%